Preparation and Optimization of Coal Fly Ash-Based Geopolymer and Its Application as an Adsorbent for Basic Yellow 2 and Methylene Blue Dyes - Eddy Heraldy; Edi Pramono; Yuniawan Hidayat; Khoirina Dwi Nugrahaningtyas; Angel Maydeleine; Intan Dwi Rahmadani (UNIVERSITAS SEBELAS MARET (UNS), 2026)
The preparation of geopolymer from coal fly ash (CFA) solid waste of Jepara PLTU has been carried out by activating CFA using a 10 M NaOH solution and Na2SiO3. Characterization of CFA and geopolymer using X-ray fluorescence (XRF), X-ray diffractometer (XRD), Scanning Electron Microscopy (SEM), and Fourier Transform Infra-Red (FTIR) spectroscopy. The adsorption process was studied under parameters including pH, geopolymer mass, contact time, and initial adsorbate concentration. The optimum conditions for the adsorption process of basic yellow 2 dye with fly ash-based geopolymer were optimum at solution pH of 11; adsorbent mass of 0.15 g; contact time of 120 minutes; and initial concentration of 80 ppm, while methylene blue adsorption was at solution pH of 11; adsorbent mass of 0.15 g; contact time of 120 minutes; and initial concentration of 60 ppm. Coal fly ash, a solid waste product from the Jepara PLTU, can be used to produce geopolymers through geopolymerization in the presence of activators such as NaOH and Na₂SiO₃. The adsorption capacities of these geopolymers for basic yellow 2 and methylene blue dye solutions are 26.55 and 19.825 mg/g, respectively.